The Olive Oil-Based Lipid Clinoleic Blocks Leukocyte Recruitment and Improves Survival during Systemic Inflammation: A Comparative In Vivo Study of Different Parenteral Lipid Emulsions - Kirsten Buschmann; Johannes Poeschl; Natascha Braach; Hannes Hudalla; Navina Kuss; David Frommhold (Mediators of Inflammation)
Although fish oil-based and olive oil-based lipid emulsions have been shown to exert anti-inflammatory functions, the immunomodulating properties of lipids are still controversial. Therefore, we investigated the anti-inflammatory effect of three different parenterally administered lipid emulsions in vivo: olive oil-based Clinoleic, fish oil-based Smoflipid, and soybean oil-based Lipofundin. We observed leukocyte recruitment in inflamed murine cremaster muscle using intravital microscopy and survival in a murine model of LPS-induced systemic inflammation and analyzed expression of leukocyte and endothelial adhesion molecules. Olive oil-based Clinoleic and fish oil-based Smoflipid profoundly inhibited leukocyte adhesion compared to Lipofundin during LPS-induced inflammation of the murine cremaster muscle. In the trauma model of cremaster muscle inflammation, Lipofundin was the only lipid emulsion that even augmented leukocyte adhesion. In contrast to Smoflipid and Lipofundin, Clinoleic effectively blocked leukocyte recruitment and increased survival during lethal endotoxemia. Flow chamber experiments and analysis of adhesion molecule expression suggest that both endothelial and leukocyte driven mechanisms might contribute to anti-inflammatory effects of Clinoleic. We conclude that the anti-inflammatory properties of Clinoleic are superior to those of Smoflipid and Lipofundin even during systemic inflammation. Thus, these results should stimulate further studies investigating parenteral lipids as an anti-inflammatory strategy in critically ill patients.